2022
DOI: 10.1136/bmjopen-2021-054145
|View full text |Cite
|
Sign up to set email alerts
|

‘We have a plan for that’: a qualitative study of health system resilience through the perspective of health workers managing antenatal and childbirth services during floods in Cambodia

Abstract: ObjectiveHealth system resilience can increase a system’s ability to deal with shocks like floods. Studying health systems that currently exhibit the capacity for resilience when shocked could enhance our understanding about what generates and influences resilience. This study aimed to generate empirical knowledge on health system resilience by exploring how public antenatal and childbirth health services in Cambodia have absorbed, adapted or transformed in response to seasonal and occasional floods.DesignA qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The hospital with the plan saw no significant change in obstetrics admissions (OR: 1.05, 95% CI (0.81 to 1.36), p=0.713), while the hospital without the plan had a large decrease in obstetrics admissions (OR 0.38, 95% CI (0.26 to 0.56), p<0.01) following the typhoon. 37 The second excluded study, Saulnier et al, 38 had similar results. 38 This qualitative study, in which researchers interviewed staff at a hospital in Cambodia, revealed that flooding had little impact on access to MHS at the facility due to the comprehensive contingency plan in place.…”
Section: Discussionmentioning
confidence: 70%
“…The hospital with the plan saw no significant change in obstetrics admissions (OR: 1.05, 95% CI (0.81 to 1.36), p=0.713), while the hospital without the plan had a large decrease in obstetrics admissions (OR 0.38, 95% CI (0.26 to 0.56), p<0.01) following the typhoon. 37 The second excluded study, Saulnier et al, 38 had similar results. 38 This qualitative study, in which researchers interviewed staff at a hospital in Cambodia, revealed that flooding had little impact on access to MHS at the facility due to the comprehensive contingency plan in place.…”
Section: Discussionmentioning
confidence: 70%
“…It should then be possible to provide potential insights on the factors that promote resilience in healthcare systems exposed to extreme perturbations, that are key to policy makers and health care managers as part of risk and vulnerability analyses. 20,21 . Each FRAM function is in essence a mathematical equation describing the requirements to pass from its input stage to its output stage.…”
Section: Discussionmentioning
confidence: 99%
“…These interviews yielded valuable insights and perspectives from individuals directly engaged in these enterprises. The researchers employed a deductive qualitative technique to establish a connection between the categories derived from the scoping review and the insights obtained from interviews conducted with pertinent stakeholders (Saulnier et al, 2022).…”
Section: Methodsmentioning
confidence: 99%